Two Cases of Progressive Familial Intrahepatic Cholestasis Type 2 Presenting with Severe Coagulopathy without Jaundice - Eric Tibesar; Christine Karwowski; Paula Hertel; Ann Scheimann; Wikrom Karnsakul (Case Reports in Pediatrics)
Progressive familial intrahepatic cholestasis (PFIC) type 2 results from a mutation in the bile salt exporter pump, impeding bile acid transport. Patients usually present with jaundice, pruritus, growth failure, and fat soluble vitamin deficiencies. We present two patients diagnosed with PFIC type 2 due to severe coagulopathy and bleeding without jaundice.